2022
DOI: 10.1007/s00784-022-04814-1
|View full text |Cite|
|
Sign up to set email alerts
|

Revised FDI criteria for evaluating direct and indirect dental restorations—recommendations for its clinical use, interpretation, and reporting

Abstract: Objectives The FDI criteria for the evaluation of direct and indirect dental restorations were first published in 2007 and updated in 2010. Meanwhile, their scientific use increased steadily, but several questions from users justified some clarification and improvement of the living document. Materials and methods An expert panel (N = 10) initiated the revision and consensus process that included a kick-off workshop and multiple online meetings by using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 109 publications
1
22
0
Order By: Relevance
“…This reliability study supported the recently initiated revision of the FDI criteria set for the evaluation of direct and indirect dental restorations [12]. The reliability tests were It was shown that (1) the intra-and inter-examiner reliability increased over the three evaluation rounds and ranged from a moderate to substantial order of magnitude and (2) Kappa estimates were found to be higher for the functional and biological categories compared to the aesthetic categories (Tables 1, 2, 3, and 4; Figs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This reliability study supported the recently initiated revision of the FDI criteria set for the evaluation of direct and indirect dental restorations [12]. The reliability tests were It was shown that (1) the intra-and inter-examiner reliability increased over the three evaluation rounds and ranged from a moderate to substantial order of magnitude and (2) Kappa estimates were found to be higher for the functional and biological categories compared to the aesthetic categories (Tables 1, 2, 3, and 4; Figs.…”
Section: Discussionsupporting
confidence: 76%
“…The expert group represented a broad spectrum of clinical and scientific experience in the field of restorative dentistry, and each of the expert contributed to the revised FDI criteria set. Details of the update process were reported elsewhere [12]. It is noteworthy that all participating experts were familiar with the concept of the FDI criteria and no specific theoretical or practical training was performed before each round of evaluation.…”
Section: Expert Groupmentioning
confidence: 99%
“…Although the FDI criteria were titled “standard criteria” for the clinical evaluation of direct and indirect restoration materials, 11 these criteria were considered confusing by other authors 29 and difficult to obtain excellent intra and inter‐examiner agreement, probably due to the five scores it presents with very subtle differences between them 30 . In 2022, 13 a revision of the FDI criteria was published, seeking to resolve the ambiguities of evaluations. However, these changes have not yet been used in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The FDI criteria 11,12 classify the restoration into four aesthetic parameters separately: gloss; marginal and superficial staining; color and translucency; aesthetic anatomical form, and the restoration can be classified as failure in any of these four parameters. The revised FDI 13 criteria consider the anatomical form of the restoration as the domain of functional properties, rather than the domain of aesthetic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation